Risk and incidence of endocrine immune-related adverse effects under checkpoint inhibitor mono- or combination therapy in solid tumors: a meta-analysis of randomized controlled trials - Vardarli, Irfan; Tan, Susanne; Brandenburg, Tim Niclas; Weidemann, Frank; Görges, Rainer; Herrmann, Ken; Führer, Dagmar (The journal of clinical endocrinology & metabolism, 2024)
Few meta-analyses on incidence of endocrine immune-related adverse effects (eirAEs) have been published and many trials have been published since.We performed a comprehensive meta-analysis with updated literature to assess risk and incidence of eirAEs of any grade and grade 3 to 5 by immune checkpoint inhibitor (ICI) monotherapy or combination therapy in solid tumors.An electronic search using PubMed/Medline, Embase, and the Cochrane Library was performed. Randomized controlled studies (RCTs) assessing eirAEs under ICI monotherapy or ICI combination therapy were selected. Stata software (v17) was used for statistical analyses and risk of bias was evaluated using Review Manager version 5.3.A total of 69 RCTs with 80 independent reports, involving 42 886 patients, were included in the study. Meta-analysis revealed the following pooled estimates for risk ratio and incidence, respectively: for any grade hypothyroidism 7.81 (95% CI, 5.68-10.74, P < .0001) and 7.64% (95% CI, 6.23-9.17, P < .0001); significantly increased also for hyperthyroidism, hypophysitis/hypopituitarism, and adrenal insufficiency; and for insulin-dependent diabetes mellitus 1.52 (95% CI, 1.07-2.18, P = .02), and 0.087% (95% CI, 0.019-0.189, P = .0006), respectively. Meta-regression showed that combination of ICIs (nivolumab plus ipilimumab; durvalumab plus tremelimumab) is an independent risk factor for any grade hypophysitis/hypopituitarism, and that ICI agent is an independent factor of risk for adrenal insufficiency, but that cancer type is not an independent risk factor for eirAEs.We showed that risk, independent from cancer type, and incidence of eirAEs are substantially increased with ICI therapy. Combination of ICIs increases risk for eirAEs, especially for hypophysitis/hypopituitarism.